China in global digital trade governance: towards a development-oriented agenda? - He, Yujia; Zeng, Ka (International Affairs, 2024)
Existing literature on the behaviour of rising powers in global trade governance has yielded inconclusive evidence about their role and impact. This article contributes to this literature by examining China's role in global digital trade governance, an issue area which so far has not received sufficient scholarly attention. Specifically, it addresses the following question: as a self-proclaimed leader of the developing world in digital development, to what extent do its preferences and negotiation approach align with the interests of other developing countries? Analysing China's participation in three sets of negotiations using process tracing, the article argues that China's dual identity both as a self-identified developing country and as a rising power has contributed to its strategic ambivalence. In principle China supports a development-oriented approach to digital trade governance, calling attention to issues such as the digital divide and preserving developing countries' policy space on data localization consistent with its domestic regulatory approaches. Yet China's interest in promoting Chinese technology firms' global expansion leads to increasing divergence with other developing countries on issues such as the e-commerce customs duty moratorium and the global taxation of digital firms, paradoxically increasing its interest alignment with developed countries and limiting its support for fundamental reforms.